PERANCANGAN KEAMANAN SISTEM MENGGUNAKAN ALGORITMA HONEYPOT PADA APLIKASI KRS ONLINE (STUDI KASUS : SEKOLAH TINGGI TEKNOLOGI ADISUTJIPTO) - Setiawan, Yoris; Sajati, Haruno; Sudibya, Bambang (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
Many colleges already apply web based academic information system use internet connection, so it is need a system security to protect from attacks such as SQL Injection and Brute Force. Honeypot is a system security which devide two system that are original and fake system. Original system used by user to access academic information system that source from correct database. While fake system used to separate hacker and user. Hackers who try to enter with SQL Injection is send to fake system directly which has wrong data. This fake system seems correct and all action that was happened in will be noted on log history. When hacker try some password ese Brute Force, system will reset user password automatically. This system already test with 79 times SQL Injection and 29 times Brute Force attack. All attacks can handle nicely with honeypot algorithm.